Age group classification based on facial images - Sai, Phyo Kyaw (2014)
There are a lot of possible real world applications where age estimation could be used. Age estimation from face images is a challenging problem since aging is a personalized process and it is also affected by many factors. Recently there is increasing interest in age estimation work but most researchers used publicly available aging face datasets most of which may not be suitable for age estimation work. First, some datasets contain face images of low quality; pose variation and extreme expression and they have limited number of images. Second, some datasets contain several images of the same person for an age. The condition makes age estimation performance on those datasets irrelevant to real world applications.